Amino acid δ15N underestimation of cetacean trophic positions highlights limited understanding of isotopic fractionation in higher marine consumers. Issue 7 (4th March 2020) - Matthews, Cory J. D.; Ruiz‐Cooley, Rocio I.; Pomerleau, Corinne; Ferguson, Steven H.
Abstract: Compound‐specific stable isotope analysis (CSIA) of amino acids (AAs) has been rapidly incorporated in ecological studies to resolve consumer trophic position (TP). Differential 15 N fractionation of "trophic" AAs, which undergo trophic 15 N enrichment, and "source" AAs, which undergo minimal trophic 15 N enrichment and serve as a proxy for primary producer δ 15 N values, allows for internal calibration of TP. Recent studies, however, have shown the difference between source and trophic AA δ 15 N values in higher marine consumers is less than predicted from empirical studies of invertebrates and fish. To evaluate CSIA‐AA for estimating TP of cetaceans, we compared source and trophic AA δ 15 N values of multiple tissues (skin, baleen, and dentine collagen) from five species representing a range of TPs: bowhead whales, beluga whales, short‐beaked common dolphins, sperm whales, and fish‐eating (FE) and marine mammal‐eating (MME) killer whale ecotypes. TP estimates (TPCSIA ) using several empirically derived equations and trophic discrimination factors (TDFs) were 1–2.5 trophic steps lower than stomach content‐derived estimates (TPSC ) for all species. Although TPCSIA estimates using dual TDF equations were in better agreement with TPSC estimates, our data do not support the application of universal or currently available dual TDFs to estimate cetacean TPs. Discrepancies were not simply due to inaccurate TDFs, however, because the difference between consumer glutamic acid/glutamine (Glx) and phenylalanine (Phe) δ 15 N values (δ 15 NGlx‐Phe ) did not follow expected TP order. In contrast to pioneering studies on invertebrates and fish, our data suggest trophic 15 N enrichment of Phe is not negligible and should be examined among the potential mechanisms driving "compressed" and variable δ 15 NGlx‐Phe values at high TPs. We emphasize the need for controlled diet studies to understand mechanisms driving AA‐specific isotopic fractionation before widespread application of CSIA‐AA in ecological studies of cetaceans and other marine consumers. Abstract : Low trophic position estimates using CSIA‐AA caution validation studies needed before widespread application to large marine consumers.